Impact of Stock Market-specific and Macro-economic Variables on Stock Return - Sapkota, Shiba Prasad (Contemporary Research: An Interdisciplinary Academic Journal, 2019)
The study was aimed to examine the impact of stock market-specific variables and macro-economic variables on stock return. It has analyzed the data of 25 countries for a period of 22 years from 1995 to 2016. The major three tests; regression analysis, co-integration analysis, and causality have been examined. The results have shown from the evidence of regression analysis and causality that the impact of the stock market-specific and macro-economic variables have been varied as per the different situation and country. Whereas, the impact of stock market-specific and macro-economic variables have been found to be consistent in the long run. Therefore, the conclusion was drawn that in the long run the relationship between stock return and stock market-specific, as well as macro-economic variables can be generalized but in the short run better not to generalize. The findings have shown that stock market-specific variables have better explaining and predicting power than macro-economic variables. In the case of stock market-specific variables, size and stock traded turnover ratio have found equally important to understand the behavior of sock return. In the case of macro-economic variables, GDPGR has found the most important variable followed by money supply, exchange rate, interest rate, trade openness, and inflation rate respectively. Finally, it has been concluded that the behavioral aspects of the investors have been missing. So, the financial theories incorporating the behavioral aspects would explain and predict better rather than economic physiognomy only.